Analisis Pengaruh Perencanaan SDM, Kepemimpinan, dan Budaya Organisasi Terhadap Revitalisasi SDM (Studi Kasus pada Dinas PUPR Bireuen) - Setia, Rizki; Iskandar, Raihan; Juanda, Juanda (Singkite Journal, 2025)
Based on empirical data, this study determines the influence of human resource planning, leadership, and organizational culture on the revitalization of human resources at the PUPR Bireuen office. The quantitative associative method was used with path analysis. The results indicate: (1) There is a direct and indirect influence of human resource planning on human resource revitalization of 36%. Meanwhile, the influence of leadership is 48.92%, and the influence of organizational culture is 34.79%. (2) Simultaneously, human resource planning, leadership, and organizational culture contribute to human resource revitalization by 58,8%. (3) The correlation analysis results indicate a causal relationship between human resource planning, leadership, and organizational culture, with a fairly strong categorization.